2005
DOI: 10.1016/j.joca.2005.04.014
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of sex differences prevalence, incidence and severity of osteoarthritis

Abstract: The results demonstrate the presence of sex differences in OA prevalence and incidence, with females generally at a higher risk. Females also tend to have more severe knee OA, particularly after menopausal age. The site differences indicate the need for further studies to explore mechanisms underlying OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

51
637
5
27

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 977 publications
(744 citation statements)
references
References 53 publications
51
637
5
27
Order By: Relevance
“…Osteoarthritis of the knee is more common in women than men [7,33]. Women lose articular cartilage at four times the annual rate of men in the proximal tibia and three times in the patella [9].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis of the knee is more common in women than men [7,33]. Women lose articular cartilage at four times the annual rate of men in the proximal tibia and three times in the patella [9].…”
Section: Introductionmentioning
confidence: 99%
“…Neck pain may become chronic in 22% of women and 16% of men and approximately 30% will lead to functional disability. Four clinical manifestations are often encountered, including: pure cervical syndrome, conjugated more commonly, basalar vertebro syndrome and rarely osteoarthritic myelopathy [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA), the most common form of arthritis, is a disabling chronic disease with significant clinical and economic implications (1)(2)(3)(4)(5). Key OA risk factors include age, sex, obesity, and trauma (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Key OA risk factors include age, sex, obesity, and trauma (6)(7)(8)(9). As the Canadian population is aging and obesity is increasing, OA incidence and prevalence are expected to continue rising (4,5,(7)(8)(9)(10). The Arthritis Alliance of Canada reported that 25% of Canadians and almost 30% of the labor force are expected to have OA by 2040 (11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation